Mill and Carlyle. An examination of Mr. John Stuart Mill's doctrine of causation in relation to moral freedom. With an occasional discourse on Sauerteig, by Smelfungus (Edinburgh, 1866)
Smelfungus is pseud. of Patrick Proctor Alexander.